Att tillfredsställa behov med personlig assistans ur ett Self-Determination Theory-perspektiv - Eriksson, Lina (2011)
Personal assistance is a part of the LSS law of individual rights and the social system in Sweden aimed to fulfill our human rights. Human rights reflect different human needs and cramping of the rights lead to unfulfilled needs. For an individual to be developed, reaching its full potential and experience well-being fulfillment of needs is crucial. Personal assistance is a social effort to bridge the difficulties caused by disability, mainly by aiming towards political values such as participation and self-determination. In this thesis the focus is on those who receive personal assistance through Luleå Kommun and is a quantitative inventory of the fulfillment of the basic needs of autonomy, competence and relatedness and experience of participation and wellbeing. The needs are strongly related to self-determination according to the Self-Determination Theory (Deci & Ryan, 2008a). The results show that the clients were quite well satisfied and experienced wellbeing to a good extent and that support for autonomy was connected to experiencing participation and feelings of relatedness. Personal assistants and the management of personal assistance have great possibilities to create a social context allowing the client to experience a realization of the political values described in the law and reach his/her full potential and experience wellbeing. Keywords: personal assistance, rights, needs, wellbeing, Self-determination theory Validerat; 20110915 (anonymous)